2007
DOI: 10.1029/2007gl031724
|View full text |Cite
|
Sign up to set email alerts
|

HF modulated ionospheric currents

Abstract: [1] The HAARP HF facility is used to modulate the components of the auroral electrojet that flow in the D-region of the ionosphere, creating ELF/VLF radiation which is then measured at a receiver co-located with the HAARP HF antenna. An HF heating model is coupled to a full wave plasma interaction FDTD code to determine the ELF/VLF response of the ionospheric plasma to the modulated HF stimulation. The predicted FDTD fields on the ground are found to be in remarkable agreement with those measured at a receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 14 publications
3
30
0
Order By: Relevance
“…The maximum change in conductivity occurs at 80 km and is equal to $80 nS m À1 (for both Pedersen and Hall components) [Payne et al, 2007]. This equals to relative changes of 22.5% for Pedersen and 3.5% for Hall components of the background conductivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum change in conductivity occurs at 80 km and is equal to $80 nS m À1 (for both Pedersen and Hall components) [Payne et al, 2007]. This equals to relative changes of 22.5% for Pedersen and 3.5% for Hall components of the background conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the electrojet currents is calculated by Payne et al [2007], for heating of the ionosphere by a sinusoidally modulated fully focused HF beam at 3.2 MHz and effective radiated power (ERP) of $24 MW. The x-axis is chosen in the eastward direction, and y-axis in the northward direction.…”
Section: Application To the Problem Of A Modulated Electrojet In An Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results with ELF and ULF waves generated by modulating the polar electrojet (PEJ) [Rietveld et al, 1984[Rietveld et al, , 1987[Rietveld et al, , 1989Papadopoulos et al, 1990Papadopoulos et al, , 2005Moore, 2007;Payne et al, 2007] indicated that the wave amplitude had a maximum in the vicinity of the heater while monotonically decreasing with distance in a fashion consistent with guided wave propagation. In general, ICD driven waves have a minimum at the ground location defined by its intersection with the magnetic field line that passes through the heated volume.…”
Section: Waves Generated By Modulated Hf Heating: Ionospheric Currentmentioning
confidence: 73%
“…A FDTD scheme was proposed by Payne [4] by coupling a HF heating model to a full wave plasma interaction FDTD code to study the ELF/VLF response of the ionospheric plasma to the modulated HF stimulation. The predicted FDTD fields on the ground are found to be in remarkable agreement with observation data.…”
Section: Introductionmentioning
confidence: 99%